Carbon nano composite phase change microcapsule with high thermal conductivity and high phase change enthalpy and preparation method thereof

By introducing thermally conductive polymers and carbon particles into the shell of the phase-change microcapsules, a thermal conductivity path is formed, which solves the problems of insufficient thermal conductivity and liquid leakage of existing phase-change microcapsules, and achieves carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change heat storage capabilities.

CN119775972AActive Publication Date: 2025-04-08HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411768302.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-08
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The thermal conductivity of existing phase-change microcapsules is insufficient, resulting in unfast heat transfer and absorption, and liquid leakage problems, limiting their practical application.

Method used

By using graphene oxide as an emulsifier, a Pickering emulsion is formed, and thermally conductive polymer cross-linked polyaniline is introduced into the microcapsule shell layer to improve the thermal conductivity of the shell layer. At the same time, carbon particles of the same size are introduced into the microcapsule to form a thermal conductivity path.

Benefits of technology

It significantly improves the thermal conductivity of microcapsules, while maintaining a high phase change enthalpy, solves the problems of insufficient thermal conductivity and liquid leakage, and enhances its application potential in the fields of thermal management and energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775972A_ABST
    Figure CN119775972A_ABST
Patent Text Reader

Abstract

The invention belongs to the related field of phase change materials, and particularly relates to a high-thermal-conductivity and high-phase-change-enthalpy carbon nano composite phase change microcapsule and a preparation method thereof. The preparation method comprises the following steps: forming an oil-in-water Pickering emulsion with graphene oxide as an interface by taking flaky graphene oxide as a dispersing agent, and adding an initiator into a water phase, so that aniline monomers and crosslinking monomers in an oil phase are polymerized on the interface of the Pickering emulsion to form a reticular polymer layer to fix a heat-conducting particle shell of the capsule. A microcapsule shell is composed of heat-conducting polymer cross-linked polyaniline and heat-conducting particle graphene oxide, the diameter of heat-conducting carbon nanoparticles dispersed into an alkane phase-change material in advance is equal to that of the capsule, a heat-conducting path of a supporting skeleton structure is formed in a confinement space in the microcapsule, and the heat-conducting property of the microcapsule is improved; the composite material has the characteristics of high heat conductivity and high phase change heat storage capacity, and can be applied to the fields of renewable energy storage, new energy vehicle heat management, industrial waste heat utilization, aerospace engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field related to phase change materials, and specifically relates to a high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsule and a preparation method thereof. The preparation and application of the composite phase change microcapsule involve the fields of thermal management, energy storage, etc. Background Art

[0002] Solid-liquid phase change materials can absorb or release a large amount of latent heat during the phase change process of near isothermal phase change, control the ambient temperature near the phase change temperature, and achieve temperature control or heat storage in a large fluctuating thermal environment. They have broad application prospects, such as renewable energy storage, thermal management of new energy vehicles, industrial waste heat utilization, aerospace engineering, etc. Alkane organic phase change materials have the advantages of high latent heat of fusion, a wide range of melting point temperatures (-5 to 66°C), non-toxicity, non-corrosiveness, stable chemical properties, small volume change during melting, and good compatibility with most materials. Therefore, they are the most widely used. The latent heat of phase change of alkane phase change materials is about 200 to 300 kJ / kg, but their thermal conductivity is generally low, with a thermal conductivity coefficient of about 0.2W / (m·K). Their low thermal conductivity makes it impossible to quickly transfer and absorb heat, and often fails to achieve the required temperature control or heat storage effect. At the same time, after melting into liquid by heat, there is also the problem of liquid leakage. As a result, solid-liquid phase change materials have long had problems such as low thermal conductivity and liquid leakage, which greatly limits the practical application of phase change materials.

[0003] Microencapsulation of phase change materials is an effective way to prevent leakage, and using thermally conductive particles as capsule walls can effectively enhance thermal conductivity. The existing technology for preparing phase change microcapsules has at least one of the following problems: the thermally conductive particles in the shell layer and the polymer used for fixing are not thermally conductive enough, and the extent to which the thermally conductive particles in the shell layer can improve the thermal conductivity is limited; in the process of forming the microcapsule wall, a large amount of polymer wrapping is required to stabilize the shell layer of the microcapsule, which significantly affects the melting enthalpy of the composite phase change microcapsule. Therefore, it is also necessary to develop a method for preparing composite phase change microcapsules that can improve the thermal conductivity of composite phase change microcapsules while maintaining their phase change enthalpy. Summary of the invention

[0004] One of the purposes of the invention is to solve the above-mentioned deficiencies and provide a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy. On the one hand, for the shell layer of the composite phase change microcapsules, graphene oxide is first used as an emulsifier to form a Pickering emulsion, and then interfacial polymerization is used to obtain thermally conductive polymer cross-linked polyaniline to stabilize carbon nanoparticles with stronger thermal conductivity to form a microcapsule shell layer, thereby improving the thermal conductivity of the shell layer; on the other hand, carbon particles with a size equivalent to the diameter of the microcapsule are introduced into the microcapsule to further form a thermal conductive path inside the microcapsule. Through the above two means, carbon nanocomposite phase change microcapsules with high thermal conductivity are obtained.

[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy, comprising the following steps:

[0006] S1, adding graphene oxide with hydrophilic surface into pure water at a mass ratio of (1-10):1000 and ultrasonically dispersing the mixture to obtain a graphene oxide dispersion;

[0007] S2, adding aniline, melamine and thermally conductive carbon nanoparticles with hydrophobic surface into an alkane phase change material, wherein the mixing mass ratio of aniline, melamine, thermally conductive carbon nanoparticles with hydrophobic surface and alkane phase change material is (2-15):(0.1-1.50):(1-10):100, and ultrasonically dispersing at a temperature higher than 5°C above the melting point of the alkane phase change material and lower than 90°C to obtain an oil phase;

[0008] S3, mixing the graphene oxide dispersion and the oil phase to obtain a mixed solution, emulsifying the mixed solution at a temperature higher than 5°C and lower than 90°C above the melting point of the alkane phase change material, adding a water-soluble initiator solution during the emulsification process, and maintaining the temperature for polymerization reaction for 5 to 20 hours after stopping the emulsification to generate an aqueous dispersion of phase change microcapsules;

[0009] S4, filtering the aqueous dispersion of the phase change microcapsules, and drying the filtered material to obtain the phase change microcapsules.

[0010] As a further improvement of the preparation method of carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy:

[0011] Preferably, in step S3, the mixing mass ratio of the graphene oxide dispersion and the oil phase is 100:(5-20).

[0012] Preferably, the surface hydrophilic graphene oxide in step S1 has a sheet diameter of 0.1 to 10 μm and a thickness of 0.5 to 20 nm.

[0013] Preferably, the thermally conductive carbon nanoparticles with hydrophobic surface in step S2 are graphene sheets or carbon nanotubes; the graphene sheets have a diameter of 5 to 20 μm and a thickness of 3 to 40 nm; the carbon nanotubes have an outer diameter of 10 to 100 nm and a length of 1 to 30 μm.

[0014] Preferably, the melting point of the alkane phase change material in step S2 is -30°C to 84°C, specifically, one or a combination of two or more of normal alkanes with 10 to 40 carbon atoms and isoalkanes with 10 to 40 carbon atoms.

[0015] Preferably, the water-soluble initiator used in step S3 is one or a combination of two or more of ammonium persulfate, potassium bromate, potassium iodate, and potassium dichromate.

[0016] Preferably, the concentration of the water-soluble initiator solution in step S3 is 30% to 60%, and 0.5 to 1.5 parts by mass of the water-soluble initiator solution is added to 10 parts by mass of the mixed solution.

[0017] Preferably, in step S3, the emulsification is performed for 5 to 10 minutes before the water-soluble initiator solution is added, and the emulsification is continued for 0.5 to 1 minute after the water-soluble initiator solution is added, and then the emulsification is stopped.

[0018] Preferably, the power of ultrasonic dispersion in steps S1 and S2 is above 500 W and the time is 30 to 120 min; and in step S4, the filtered material is freeze-dried or air-dried at low temperature.

[0019] The second object of the present invention is to provide a carbon nanocomposite phase change microcapsule with high thermal conductivity and high phase change enthalpy obtained by the preparation method of the carbon nanocomposite phase change microcapsule with high thermal conductivity and high phase change enthalpy as described in any one of the above.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The present invention provides a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy. First, graphene oxide is dispersed in pure water to obtain a graphene oxide dispersion. Aniline, melamine (crosslinking agent) and thermally conductive carbon nanoparticles are added to an alkane phase change material, and ultrasonically dispersed at a temperature 5°C higher than the melting point of the phase change material but not exceeding 90°C to obtain an oil phase. Secondly, for the shell layer of the composite phase change microcapsule, the graphene oxide dispersion and the oil phase are mixed, and graphene oxide is used as an emulsifier to form a water-in-oil Pickering emulsion with graphene oxide as the interface. The internal phase of the Pickering emulsion is an alkane phase change material containing carbon nano thermal conductive particles, aniline monomers and crosslinking monomers. Then, an initiator is further added to the water phase to polymerize the aniline monomer and the cross-linking monomer in the oil phase at the interface of the Pickering emulsion to form a network layer of thermally conductive polymer cross-linked polyaniline to stabilize the carbon nanoparticles with stronger thermal conductivity to form a microcapsule shell layer, thereby improving the thermal conductivity of the shell layer.

[0022] 2) The microcapsule shell is composed of thermally conductive polymer cross-linked polyaniline and thermally conductive particles graphene oxide. Due to the lamellar structure of graphene oxide and the interfacial polymerization of polyaniline, the amount of thermally conductive particles and polymers required to form the thermally conductive capsule wall of the microcapsule is relatively small, which can improve the thermal conductivity of the microcapsule while maintaining a higher phase change enthalpy of the nanocomposite phase change microcapsule; the diameter of the thermally conductive carbon nanoparticles first dispersed in the alkane phase change material is equivalent to the capsule diameter, forming a thermal conductive path supporting the skeleton structure in the confined space inside the microcapsule. The addition of a small amount of thermally conductive carbon nanoparticles can significantly improve the thermal conductivity of the microcapsule. Through the above two means, a carbon nanocomposite phase change microcapsule with high thermal conductivity and high phase change enthalpy is obtained.

[0023] Therefore, the composite phase change microcapsules of the present invention have the characteristics of high thermal conductivity and high phase change heat storage capacity, and can be applied to renewable energy storage, thermal management of new energy vehicles, industrial waste heat utilization, aerospace engineering and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The flowchart of the preparation method of a high thermal conductivity carbon nanocomposite phase change microcapsule of the present invention is as follows: Figure 1 In a, a is a flow chart of the preparation method of nanocomposite phase-change microcapsules containing graphene in the inner phase of Example 1 and the scanning electron microscope morphology of the nanocomposite phase-change microcapsules. Figure 1 Part b is a flow chart of the preparation method of nanocomposite phase-change microcapsules containing carbon nanotubes in the inner phase of Example 5 and the scanning electron microscope morphology of the nanocomposite phase-change microcapsules.

[0025] Figure 2 The comparison of thermal conductivity of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 1-4 after tabletting;

[0026] Figure 3 The comparison of the melting enthalpy of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 1-4;

[0027] Figure 4 The comparison of thermal conductivity of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 5-8 after tabletting;

[0028] Figure 5 It is a comparison of the melting enthalpy of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 5-8. DETAILED DESCRIPTION

[0029] The present invention will be described in detail below in conjunction with the accompanying drawings, and the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments made by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a method for preparing high thermal conductive carbon nanocomposite phase change microcapsules through improvement. The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention by referring to the description.

[0031] Comparative Example

[0032] This comparative example provides a method for preparing phase change microcapsules, which specifically comprises the following steps:

[0033] S1, dispersing 0.4 g of graphene oxide with a sheet diameter of 5 to 10 μm, a thickness of 4 to 20 nm, and a hydrophilic surface in 80 g of pure water, and ultrasonically dispersing at a power of 600 W for 120 min to obtain a graphene oxide dispersion;

[0034] S2, adding 0.8 g of aniline and 0.048 g of melamine to 8 g of eicosane, and dispersing them ultrasonically at 50° C. and 600 W for 2 h to obtain an oil phase containing aniline monomer and crosslinking agent melamine;

[0035] S3, adding the oil phase to the graphene oxide dispersion, emulsifying at 50°C for 10 min, the speed of the emulsifier is 12000 rpm, adding 8 g of 50% ammonium persulfate aqueous solution, continuing emulsification for 0.5 min and then stopping the emulsification, maintaining the polymerization reaction at 50°C for 14 h, and generating an aqueous dispersion of phase change microcapsules;

[0036] S4. Filter the aqueous dispersion of the phase change microcapsules, and freeze-dry them to obtain the phase change microcapsules.

[0037] Example 1

[0038] This embodiment provides a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy, which specifically includes the following steps:

[0039] S1, dispersing 0.4 g of graphene oxide with a sheet diameter of 5 to 10 μm, a thickness of 4 to 20 nm, and a hydrophilic surface in 80 g of pure water, and ultrasonically dispersing at a power of 600 W for 120 min to obtain a graphene oxide dispersion;

[0040] S2, adding 0.8 g of aniline, 0.048 g of melamine and 0.16 g of graphene with a thickness of 4 to 20 nm and a hydrophobic surface to 8 g of eicosane, and dispersing them ultrasonically at 600 W for 120 min at 50° C. to obtain an oil phase containing aniline monomer, crosslinking agent melamine and graphene;

[0041] S3, adding the oil phase to the graphene oxide dispersion, emulsifying at 50°C for 10 min, the speed of the emulsifier is 12000 rpm, adding 8 g of 50% ammonium persulfate aqueous solution, continuing emulsification for 0.5 min and then stopping the emulsification, maintaining the polymerization reaction at 50°C for 14 h, and generating an aqueous dispersion of phase change microcapsules;

[0042] S4, filtering the aqueous dispersion of the phase change microcapsules, freeze-drying the filtered material, and obtaining composite phase change microcapsules.

[0043] Example 2

[0044] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Embodiment 1, except that 0.32 g of graphene with a thickness of 4 to 20 nm and a hydrophobic surface is added in step S2 to finally obtain composite phase-change microcapsules.

[0045] Example 3

[0046] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Embodiment 1, except that 0.48 g of graphene with a thickness of 4 to 20 nm and a hydrophobic surface is added in step S2 to finally obtain composite phase-change microcapsules.

[0047] Example 4

[0048] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Embodiment 1, except that 0.64 g of graphene with a thickness of 4 to 20 nm and a hydrophobic surface is added in step S2 to finally obtain composite phase-change microcapsules.

[0049] Figure 2 It is a comparison of the thermal conductivity of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 1-4 after tabletting; Figure 3 It is a comparison of the melting enthalpy of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 1-4. Figure 2 and Figure 3 It can be seen that the internal phase of the composite phase-change microcapsules prepared in the comparative example does not contain carbon nanoparticles, and the thermal conductivity measured after tableting is 0.99W / (m·K); the internal phase of the composite phase-change microcapsules prepared in Examples 1-4 contains graphene particles of similar size to the microcapsules, and the thermal conductivity measured after tableting is 1.18-2.25W / (m·K), and the thermal conductivity is significantly improved, and the highest thermal conductivity is more than twice that of the comparative example. At the same time, the melting enthalpy of the composite phase-change microcapsules prepared in Examples 1-4 is 228.0-243.6J / g, maintaining a relatively high level.

[0050] Example 5

[0051] This embodiment provides a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy, which specifically includes the following steps:

[0052] S1, dispersing 0.40 g of graphene oxide with a sheet diameter of 5 to 10 μm, a thickness of 4 to 20 nm, and a hydrophilic surface in 80 g of pure water, and ultrasonically dispersing at a power of 600 W for 120 min to obtain a graphene oxide dispersion;

[0053] S2, adding 0.8 g of aniline, 0.048 g of melamine and 0.16 g of carbon nanotubes with an outer diameter of 50-100 nm, a length of 1-15 μm and a hydrophobic surface to 8 g of eicosane, and dispersing them ultrasonically at 600 W for 120 min at 50° C. to obtain an oil phase containing aniline monomer, crosslinking agent melamine and carbon nanotubes;

[0054] S3, adding the oil phase to the graphene oxide dispersion, emulsifying at 50°C for 10 min, the speed of the emulsifier is 12000 rpm, adding 8 g of 50% ammonium persulfate aqueous solution, continuing emulsification for 0.5 min and then stopping the emulsification, maintaining the polymerization reaction at 50°C for 14 h, and generating an aqueous dispersion of phase change microcapsules;

[0055] S4, filtering the aqueous dispersion of the phase change microcapsules, freeze-drying the filtered material, and obtaining composite phase change microcapsules.

[0056] Example 6

[0057] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Example 5, except that 0.32 g of carbon nanotubes with an outer diameter of 50-100 nm, a length of 1-15 μm, and a hydrophobic surface are added in step S2. Finally, composite phase-change microcapsules are obtained.

[0058] Example 7

[0059] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Example 5, except that 0.48 g of carbon nanotubes with an outer diameter of 50-100 nm, a length of 1-15 μm, and a hydrophobic surface are added in step S2 to finally obtain composite phase-change microcapsules.

[0060] Example 8

[0061] This embodiment provides a method for preparing carbon nanocomposite phase-change microcapsules with high thermal conductivity and high phase-change enthalpy. The specific steps are similar to those of Example 5, except that 0.64 g of carbon nanotubes with an outer diameter of 50-100 nm, a length of 1-15 μm, and a hydrophobic surface are added in step S2 to finally obtain composite phase-change microcapsules.

[0062] Figure 4 The comparison of thermal conductivity of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 5-8 after tabletting; Figure 5 The comparison of the melting enthalpy of the phase change microcapsules prepared in the comparative example and the nanocomposite phase change microcapsules prepared in Examples 5-8 is shown in FIG. Figure 4 and Figure 5It can be seen that the thermal conductivity of the composite phase change microcapsules obtained in Examples 5-8 after tableting is 1.15-1.60 W / (m·K), which is significantly improved compared with the thermal conductivity of 0.99 W / (m·K) of the composite phase change microcapsules obtained in the comparative example. At the same time, the melting enthalpy of the composite phase change microcapsules obtained in Examples 5-8 is 231.2-242.3 J / g, which is slightly lower than the melting enthalpy of 243.6 J / g of the composite phase change microcapsules obtained in the comparative example, but maintains a relatively high level.

[0063] Example 9

[0064] This embodiment provides a method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy, which specifically includes the following steps:

[0065] S1, dispersing 10 g of graphene oxide with a sheet diameter of 0.1 to 5 μm, a thickness of 0.5 to 20 nm, and a hydrophilic surface in 1000 g of pure water, and ultrasonically dispersing at a power of 600 W for 30 min to obtain a graphene oxide dispersion;

[0066] S2, adding 2 g of aniline, 0.1 g of cross-linking agent melamine, and 10 g of hydrophobic graphene with a sheet diameter of 5 to 20 μm and a thickness of 3 to 40 nm to 100 g of pentadecane, and ultrasonically dispersing at a power of more than 500 W for 30 min at 30° C. to obtain an oil phase containing aniline monomer, cross-linking agent melamine and graphene;

[0067] S3, adding the oil phase to the graphene oxide dispersion, emulsifying at 30°C for 10 minutes, the speed of the emulsifier is 5000 rpm, adding 10g of 30% potassium bromate solution by mass, stopping the emulsification after 0.5 minutes, maintaining the polymerization reaction at 30°C for 10 hours, and generating an aqueous dispersion of phase change microcapsules;

[0068] S4, filtering the aqueous dispersion of the phase change microcapsules, and air-drying the microcapsules at low temperature to obtain phase change microcapsules.

[0069] The thermal conductivity of the composite phase-change microcapsules obtained in Example 9 after tableting is measured at 1.88 W / (m·K), which is significantly improved compared with the thermal conductivity of 0.99 W / (m·K) of the composite phase-change microcapsules obtained in the comparative example. At the same time, the melting enthalpy of the composite phase-change microcapsules obtained in Example 9 is 212 J / g, which is slightly lower than the melting enthalpy of 243.6 J / g of the composite phase-change microcapsules obtained in the comparative example, but maintains a relatively high level.

[0070] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy, characterized in that: The following steps are involved: S1, adding graphene oxide with hydrophilic surface into pure water at a mass ratio of (1-10):1000 and ultrasonically dispersing the mixture to obtain a graphene oxide dispersion; S2, adding aniline, melamine and thermally conductive carbon nanoparticles with hydrophobic surface into an alkane phase change material, wherein the mixing mass ratio of aniline, melamine, thermally conductive carbon nanoparticles with hydrophobic surface and alkane phase change material is (2-15):(0.1-1.50):(1-10):100, and ultrasonically dispersing at a temperature higher than 5°C above the melting point of the alkane phase change material and lower than 90°C to obtain an oil phase; S3, mixing the graphene oxide dispersion and the oil phase to obtain a mixed solution, emulsifying the mixed solution at a temperature higher than 5°C and lower than 90°C above the melting point of the alkane phase change material, adding a water-soluble initiator solution during the emulsification process, and maintaining the temperature for polymerization reaction for 5 to 20 hours after stopping the emulsification to generate an aqueous dispersion of phase change microcapsules; S4, filtering the aqueous dispersion of the phase change microcapsules, and drying the filtered material to obtain the phase change microcapsules.

2. The method for preparing the carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy according to claim 1, characterized in that: In step S3, the mixing mass ratio of the graphene oxide dispersion and the oil phase is 100:(5-20).

3. The method for preparing the high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsules according to claim 1, characterized in that: The hydrophilic graphene oxide sheet in step S1 has a diameter of 0.1 to 10 μm and a thickness of 0.5 to 20 nm.

4. The method for preparing the high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsules according to claim 1, 2 or 3, characterized in that: The thermally conductive carbon nanoparticles with hydrophobic surfaces in step S2 are graphene sheets or carbon nanotubes; the graphene sheets have a diameter of 5 to 20 μm and a thickness of 3 to 40 nm; the carbon nanotubes have an outer diameter of 10 to 100 nm and a length of 1 to 30 μm.

5. The method for preparing the high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsules according to claim 1, 2 or 3, characterized in that: The melting point of the alkane phase change material in step S2 is -30°C to 84°C, specifically, it is one or a combination of two or more of normal alkanes with 10 to 40 carbon atoms and isoalkanes with 10 to 40 carbon atoms.

6. The method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy according to claim 1, characterized in that: The water-soluble initiator used in step S3 is one or a combination of two or more of ammonium persulfate, potassium bromate, potassium iodate, and potassium dichromate.

7. The method for preparing the high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsules according to claim 1 or 6, characterized in that: The concentration of the water-soluble initiator solution in step S3 is 30% to 60%, and 0.5 to 1.5 parts by weight of the water-soluble initiator solution is added to 10 parts by weight of the mixed solution.

8. The method for preparing carbon nanocomposite phase change microcapsules with high thermal conductivity and high phase change enthalpy according to claim 1 or 2, characterized in that: In step S3, the emulsification is performed for 5 to 10 minutes before the water-soluble initiator solution is added, and the emulsification is continued for 0.5 to 1 minute after the water-soluble initiator solution is added, and then the emulsification is stopped.

9. The method for preparing the high thermal conductivity and high phase change enthalpy carbon nanocomposite phase change microcapsules according to claim 1 or 2, characterized in that: In steps S1 and S2, the power of ultrasonic dispersion is above 500 W and the time is 30 to 120 minutes; in step S4, the filtered material is freeze-dried or air-dried at low temperature.

10. A carbon nanocomposite phase change microcapsule with high thermal conductivity and high phase change enthalpy obtained by the method for preparing the carbon nanocomposite phase change microcapsule with high thermal conductivity and high phase change enthalpy as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Phase change microcapsule based on polymer shell layer and manufacturing method thereof

    CN111774017A

  • PW (at) PS / BNNSs phase change microcapsule with excellent heat conduction and heat storage performance and preparation method of PW (at) PS / BNNSs phase change microcapsule

    CN115491181A

  • Hydrophobic and antistatic carbon nanotube functional coating as well as preparation method and application thereof

    CN117363217A

  • Phase-change microcapsule coated with heat-conducting granules and preparation method of phase-change microcapsule

    CN118165707A

  • microcapsules

    WO2019145731A1